2023
DOI: 10.3390/molecules28124877
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Metabolomic Analyses Reveal the Effects of Grafting on Special Metabolites of Acanthopanax senticosus Leaves

Abstract: Acanthopanax senticosus (A. senticosus) is a member of Acanthopanax Miq. and is used in traditional Chinese medicine, and it has been found that grafting technology can be used to alter plant metabolite composition and transcriptome characteristics. In this study, shoots of A. senticosus were grafted onto the rootstocks of the vigorous Acanthopanax sessiliflorus (A. sessiliflorus) to improve its varietal characteristics. In order to investigate the changes in metabolites and transcriptional patterns in grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…This suggests that the upregulated DXR gene expression in C. camphora could lead to an increase in terpenoid content (Du et al, 2022). Wang et al (2023) indicated that the OfDXR gene is very important for making terpenoid compounds and that overexpressing it in Arabidopsis plants during the main or full blooming stage led to a rise in the total amount of terpenoid compounds. Zhang et al (2022) found that DXS, DXR, and ispH in the MEP pathway and GGPS were significantly expressed in summer Chinese cedar (SCC) needles and increased the accumulation of terpenoids, notably diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the upregulated DXR gene expression in C. camphora could lead to an increase in terpenoid content (Du et al, 2022). Wang et al (2023) indicated that the OfDXR gene is very important for making terpenoid compounds and that overexpressing it in Arabidopsis plants during the main or full blooming stage led to a rise in the total amount of terpenoid compounds. Zhang et al (2022) found that DXS, DXR, and ispH in the MEP pathway and GGPS were significantly expressed in summer Chinese cedar (SCC) needles and increased the accumulation of terpenoids, notably diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the upregulated DXR gene expression in C. camphora could lead to an increase in terpenoid content (Du et al, 2022). Wang et al (2023) indicated that the OfDXR gene is very important for making terpenoid compounds and that overexpressing it in Arabidopsis plants during the main or full blooming stage led to a rise in the total amount of terpenoid compounds. Zhang et al (2022) found that DXS, DXR, and ispH in the MEP pathway and GGPS were significantly expressed in summer Chinese cedar (SCC) needles and increased the accumulation of terpenoids, notably diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…balsamifera DC has grown abundantly for medicine and cosmetics recently (Pang et al, 2014;Jirakitticharoen et al, 2022). The metabolite accumulation pattern of B. balsamifera DC could be affected by cultivating conditions and the external environment (Wang et al, 2023). Research revealed that the content of L-borneol was different in different tissues at different developmental stages (Pang et al, 2017;Guan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the upregulated DXR gene expression in C. camphora could lead to an increase in terpenoid content (Du et al, 2022). Wang et al (2023) indicated that the OfDXR gene is very important for making terpenoid compounds and that overexpressing it in Arabidopsis plants during the main or full blooming stage led to a rise in the total amount of terpenoid compounds. Zhang et al (2022) found that DXS, DXR, and ispH in the MEP pathway and GGPS were significantly expressed in summer Chinese cedar (SCC) needles and increased the accumulation of terpenoids, notably diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…balsamifera DC has grown abundantly for medicine and cosmetics recently (Pang et al, 2014;Jirakitticharoen et al, 2022). The metabolite accumulation pattern of B. balsamifera DC could be affected by cultivating conditions and the external environment (Wang et al, 2023). Research revealed that the content of L-borneol was different in different tissues at different developmental stages (Pang et al, 2017;Guan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%